Control Measures for Continuous Deep Sedation Until Death: A Framing Analysis of the Views of Physicians. (November 2021) - Vissers, Stijn; Robijn, Lenzo; Dierickx, Sigrid; Mortier, Freddy; Cohen, Joachim; Deliens, Luc; Chambaere, Kenneth
Physicians have been subject to increasing external control to improve their medical practice, and scholars have theorized extensively about their opposition to such control. However, little empirical attention has been paid to the views and reasoning that lie behind this opposition. An in-depth understanding is necessary for enhancing the effectiveness and efficiency of external controls, and continuous deep sedation until death (CDS) is an interesting case in this regard. This study aims to explore how physicians frame control measures for CDS. We conducted 47 semi-structured interviews with Belgian physicians in 2019. A qualitative framing analysis was performed to analyze their views and reasoning. This study reveals that physicians approach CDS practice and control measures with different emphases. Controlling by mechanisms of professional self-regulation and state governance are put forward as appropriate means to improve CDS practice. Policymakers should take into consideration physicians' frames to develop sound control measures.